China's strategy for the development of renewable energies. Issue 11 (2nd November 2017) - Liu, Zhenling
ABSTRACT: Becoming a net importer of crude oil has encouraged China to develop new energy systems for heat and power generation. Increasing crude oil prices have increased the potential wide influence on China's economic growth. This article explores the influence of domestic renewable energy policy regarding the China Energy Outlook for the years 2015–2035. Applying the national roadmap of renewable energy, three scenarios are constructed: wind energy, biomass energy, and solar energy. The advantages and disadvantages of these scenarios are studied and some suggestions are proposed to improve the economic aspects of renewable energy development.